NiO/Nb2O5/C Hydrazine Electrooxidation Catalysts for Anion Exchange Membrane Fuel Cells. Issue 4 (1st January 2017) - Sakamoto, Tomokazu; Masuda, Teruyuki; Yoshimoto, Koji; Kishi, Hirofumi; Yamaguchi, Susumu; Matsumura, Daiju; Tamura, Kazuhisa; Hori, Akihiro; Horiuchi, Yousuke; Serov, Alexey; Artyushkova, Kateryna; Atanassov, Plamen; et al.
Abstract : NiO/Nb2 O5 /C (8:1), (4:1), (2:1), NiO/C, and Ni/C catalysts for hydrazine electrooxidation were synthesized by an evaporation drying method followed by thermal annealing. Prepared catalysts were characterized by X-ray diffraction (XRD), high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM), energy dispersive X-ray spectrometry (EDS), and X-ray absorption fine structure (XAFS). Catalytic activity, durability, and selectivity in the reaction of hydrazine electrooxidation were evaluated in alkaline media. The highest catalytic activity in mentioned above reaction was found for Ni/C, followed by: NiO/Nb2 O5 /C (8:1), NiO/Nb2 O5 /C (4:1). NiO/Nb2 O5 /C (2:1) whiles NiO/C has almost no activity for hydrazine oxidation. NiO/Nb2 O5 /C (8:1) and (4:1) had a highest stability during electrooxidation of hydrazine at 60°C. It was explained by oxygen defect of NiO in NiO/Nb2 O5 /C from XAFS analysis. The selectivity hydrazine electrooxidation as measured by ammonia production resulted in observation that metallic Ni surface facilitates N-N bond breaking of hydrazine, which was confirmed by density functional theory (DFT) calculations.